Implementasi Kebijakan Transportasi Publik Bus Listrik Dalam Mengurangi Kemacetan Di Kota Medan - Olivia, Anggi Ananda; Panjaitan, Maringan; Dedona, Laurencia Primawati (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
: The implementation of public transportation policies in Medan City, particularly through the introduction of electric buses, aims to tackle the increasing problem of traffic congestion. This study evaluates the execution of this policy and its effects on traffic flow. The results show that the policy encompasses the establishment of infrastructure, including dedicated bus lanes and charging stations; however, challenges persist regarding coordination among agencies and efforts to engage the public. Electric buses have considerable potential to alleviate congestion due to their greater passenger capacity compared to private vehicles. The effectiveness of this policy is also affected by factors such as population density and travel behaviors. Consequently, it is essential to improve public awareness of the advantages of eco-friendly transportation. In summary, this policy requires enhanced support from the government, community, and private sector to positively influence mobility and environmental outcomes.